Studies on Mixed Ligand Complexes of Oxovanadium(IV) with 2-(3´ -Phenyl-5´ -Chloro Indole-2´ -Carboxamidyl)Iminomethyl Furan as Primary and 2-Carboxyphenyl-Azo-β-Naphthyl Amine as Secondary Ligand - K. Agarwal, Suresh (Asian Journal of Chemistry, 2010)
A polydentate Schiff base ligand, 2-(3´-phenyl-5´-chloro indole-2´-carboxamidyl) iminomethyl furan, has been prepared by the condensation of 3-phenyl-5-chloro indole-2-carboxyhydrazide and furfural. A number of oxovanadium(IV) complexes have been synthesised by the interaction of vanadyl salts with the Schiff base as primary and 2-carboxyphenyl-azo-β-naphthyl amine as secondary ligand. The isolated mixed ligand complexes are characterised by elemental analysis, magnetic, spectral and thermogravimetric studies. Analytical data suggest the formulae (VOLL´)X [where L = C20H14N3O2Cl, L´ = C17H12N3O2 and X = Cl, Br, I, NO3, NCS, ClO4] for the isolated complexes. The Λm values of the complexes lie in the range 102.2–106.8 ohm–1 cm2 mol–1 in DMSO at the concentration 10–3 M indicating that these are 1 : 1 electrolytes. IR spectra suggest that the Schiff base and azo compound serve as tridentate and bidentate ligands respectively in the formation of complexes. Magnetic and reflectance spectral studies show that the complexes possess distorted octahedral geometry. TGA shows the decomposition of the complexes in 300-570ºC temperature range. V2O5 is obtained as the final product in each case. The screening of the complexes and ligands against organisms such as E. coli and S. aureus shows that the complexes are more active than the ligands.